Censorship detected in ET (Ethiopia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Ethiopia. Data sourced from OONI.
Censorship Incident ID: ET-2026-0710. Severity: critical. Confidence: 70%